2020
DOI: 10.3390/s20092692
|View full text |Cite
|
Sign up to set email alerts
|

Railway Point-Operating Machine Fault Detection Using Unlabeled Signaling Sensor Data

Abstract: In this study, we propose a methodology for the identification of potential fault occurrences of railway point-operating machines, using unlabeled signal sensor data. Data supplied by Network Rail, UK, is processed using a fast Fourier transform signal processing approach, coupled with the mean and max current levels to identify potential faults in point-operating machines. The method developed can dynamically adapt to the behavioral characteristics of individual point-operating machines, thereby providing bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Effective protection assures good turnout function and contributes to rail traffic efficiency and safety [ 23 , 24 , 25 , 26 ]. Some researchers have also proposed different incremental methods for classification problems [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Effective protection assures good turnout function and contributes to rail traffic efficiency and safety [ 23 , 24 , 25 , 26 ]. Some researchers have also proposed different incremental methods for classification problems [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The statistical data on derailments confirm the claim in [83] that derailments are common. Mistry et al in [84] concluded that railway point-operating machine (POM) failures are considered to be critical failures of a rail network system. Signaling equipment and turnout failures account for 55% of all railway infrastructure component failures, leading to delays, costly repairs, and potentially hazardous situations.…”
Section: Structure Of the Number Of Derailments And Safety Statusmentioning
confidence: 99%
“…For instance, in the example of engine wear, it is feasible to obtain degradation data through sensor technology, then employ data mining and machine learning algorithms to determine life span and maintenance decisions [6,7,10]. Several reports in the literature discuss using machine learning and statistical modelling to predict wear and failure [11], although work specifically on engine failure rates is not so common, the reports discovered are briefly discussed herein.…”
Section: Introductionmentioning
confidence: 99%